Impact of provider-selected indication requirement on urine test utilization and positivity - Jessica A. Penney; Angie Mae Rodday; Paola Sebastiani; David R. Snydman; Shira I. Doron (Cambridge University Press, 2022)
Abstract Objective: To evaluate the impact of the addition of an indication specification requirement to isolated urine-culture ordering on testing utilization. Design: Retrospective study utilizing interrupted time series analysis with negative binomial regression. The preintervention period was October 1, 2018-November 11, 2019, and the postintervention period was November 12, 2019-October 31, 2020. The primary outcome was isolated culture rate per 1,000 patient days. Secondary outcomes were the proportion of all urine tests ordered as isolated urine culture and culture positivity. An exploratory analysis assessed the appropriateness of selected testing indications. Setting: A 415-bed, urban, academic medical center. Patients: Adult patients with urine testing performed during hospital admission. In total, 1,494 unique isolated urine-culture orders were included in the analysis. Interventions: On November 12, 2019, the laboratory order interface was changed to require the ordering provider to select an indication for isolated urine culture. Results: Isolated urine-culture rates did not significantly change after the intervention (11.2-7.8 cultures per 1,000 patient days; P = .17) nor did culture positivity (26.9% vs 26.8%). Most ordering providers left the indication for testing blank, and of those charts reviewed, 67% did not have a documented condition for which isolated urine culture was the most appropriate initial test. Conclusions: The addition of an order-specification requirement for isolated urine-culture testing did not significantly affect ordering practices. The test remains overused as the initial diagnostic evaluation for a suspected urinary tract infection. Further provider education and continued changes in provider workflow are needed to achieve lasting change in practice.